Learning styles and supervision: A critical review. Issue 2 (3rd July 2018) - Tangen, Jodi L.
ABSTRACT: Attending to supervisees' learning styles is a noted component of supervision best practices. However, the extant literature on learning styles is complex and controversial, leaving supervisors with little direction on whether or not—or how—to use them. In the following critical review, the literature on learning styles is reviewed and discussed, and recommendations for supervision practice and future research are provided.